2023
DOI: 10.1002/adfm.202302770
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Mediated Lattice Rotation Design for Enhancing Thermoelectric Performance in Bi2S2Se

Abstract: A unique strain-mediated lattice rotation strategy is introduced via nanocompositing to upsurge the optimized limits in the composition-to-structural pathway on rationally engineering the efficient thermoelectric material. In this study, a special lattice rotation via strain engineering is realized to optimize the desired electronic and chemical environment for enhancing thermoelectric properties in n-type Bi 2 S 2 Se. This approach results in a unique transport phenomenon to assist high-energy electrons in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The band structure and density of states (DOS) for both samples are illustrated in Figure . The band gap of pure Bi 2 S 2 Se was found to be approximately 0.96 eV consistent with previous studies. , As shown in Figure a, Bi 2 S 2 Se exhibited a clear energy band merging phenomenon compared to Bi 2 S 3 , along with a slightly reduced band gap, which could explain the higher conductivity of Bi 2 S 2 Se compared to Bi 2 S 3 . Both Bi 2 S 2 Se and Bi 2 S 3 are indirect band gap semiconductors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band structure and density of states (DOS) for both samples are illustrated in Figure . The band gap of pure Bi 2 S 2 Se was found to be approximately 0.96 eV consistent with previous studies. , As shown in Figure a, Bi 2 S 2 Se exhibited a clear energy band merging phenomenon compared to Bi 2 S 3 , along with a slightly reduced band gap, which could explain the higher conductivity of Bi 2 S 2 Se compared to Bi 2 S 3 . Both Bi 2 S 2 Se and Bi 2 S 3 are indirect band gap semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…25 Bi 2 S 2 Se possesses the orthorhombic crystal structure with a Pnma space group, which is consistent with that of the Bi 2 S 3 material system. 25,26 The ZT value was successfully optimized from 0.18 to 0.36. In the research conducted by Li et al, it was found that incorporating a small amount of BiI 3 (0.7 vol %) leads to a remarkable decrease of approximately 72% in the lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…From a crystallographic standpoint, lattice rotation refers to displacement of the momentum transfer in the 3D reciprocal space in directions orthogonal to the displacement caused by lattice strain ( 28 ). Lattice rotation is commonly associated with the formation of defects and is prevalent in battery materials as a means to accommodate the heterogeneous electrochemical reactions ( 29 , 30 ). Despite its prevalence, its impact on the structural failure and capacity decay is much less understood compared with that of lattice strain owing to difficulties for its characterization by conventional methods.…”
Section: Unrecoverable Lattice Rotation Induces Structure Degradationmentioning
confidence: 99%
“…The thermoelectric (TE) approach is now progressively recognized as a significant green energy source. One of the most important methods for effectively harvesting a massive quantity of waste heat is the primary use of thermoelectric resources, which have the potential to directly convert waste heat energy into electricity. The dimensionless figure of merit ( ZT = σ S 2 T /κ) determines the efficiency of TE materials, where T , S , σ, and κ represent the absolute temperature, the thermopower, the electrical conductivity, and total thermal conductivity, respectively, whereas, total thermal conductivity (κ) is the combined effect (κ = κ e + κ L ) of the electronic part of thermal conductivity (κ e ) and the lattice thermal conductivity (κ L ). As a result of the coupling between the TE transport parameters, it is a great challenge to achieve large ZT values. To obtain high ZT , one must simultaneously lower thermal conductivity (κ is also expressed as κ = C P Dd where, C P , D , and d are specific heat, thermal diffusivity, and density, respectively) and enhance power factor PF (PF = σ S 2 ). However, the PF may be increased by enhancing electrical conductivity (σ), thermopower ( S ), or both through optimization of carrier concentration and band-structure engineering. The low lattice thermal conductivity can be attained by using various methods, such as nanoincorporations and defect engineering, etc. ,, However, it is difficult to achieve significant PF enhancement and significant reduction of thermal conductivity concurrently due to fundamental coupling within TE parameters (κ, S , and σ) by utilizing a simple approach.…”
Section: Introductionmentioning
confidence: 99%